Hubungan Pengetahuan Ibu terhadap Interprestasi Hasil KPSP Anak Usia 0-24 Bulan - Sagita Darma Sari; Wera Astriani (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
The period of infancy and toddler is an important period in the growth and development of children. It is very important for parents to know the child’s developments as a basis for knowing further developments. The purpose of this study was to determine the relationship of maternal knowledge on the interpretation of the results of KPSP children aged 0-24 months at BPM Sagita Darma Sari Palembang. The design of this research is quantitative descriptive with cross sectional approach with a sample of 88 respondents selected by purposive sampling. Data collection by questionnaire and processed by Spearman rank test. The results of this study indicate that there is a significant relationship between mother's knowledge and KPSP interpretation of children aged 0-24 months whose p value = 0,000 is smaller than a 0.05 (p va). Researchers recommend that health workers, especially at BPM Sagita Darma Sari Palembang to further enhance the early detection of child growth and development, so that if there is a delay in the development of children can take precautionary steps earlier.